A Definition of “Multitargeticity”: Identifying Potential Multitarget and Selective Ligands Through a Vector Analysis - Sánchez-Tejeda, Juan Francisco; Sánchez-Ruiz, Juan F.; Salazar, Juan Rodrigo; Loza-Mejía, Marco A. (Frontiers in Chemistry, 2020)
Design of multitarget drugs is an important area of research in Medicinal Chemistry, as they have been proposed as potential therapeutics for the management of complexes diseases. However, a definition of what is a multitarget drug is not an easy task. In this work, we propose the implementation of a vector analysis for measuring “multitargeticity.” We developed some terms like order and force of a ligand to finally reach a two parameters multitarget indexes 1 and 2 (MTi1 and MTi2). The combination of these two parameters allows the discrimination of multitarget drugs. Among the strengths of this metric are that it could be used independently of the parameters used for in silico or experimental bioactivity and that it provides a measure for identifying true multitarget compounds. We tested this index to evaluate a virtual library of potential ligands to some target related to multiple sclerosis, identifying 10 compounds that are plausible leads for the development of multitarget drugs based on their in silico behavior.